The Asymptotic Behavior of Viscous Incompressible Fluid Small Oscillations with Solid Interacting Particles - Berezhnyi, M. A. (Журнал математичної фізики, аналізу, геометрії, 2007)
The motion of viscous incompressible fluid with a large number of small solid interacting particles is considered. The asymptotic behavior of small oscillations of the system is studied, when the radii of particles, distances between the nearest particles and their interaction power are decreased in the prescribed way. The equations describing the homogenized model of the system are derived.Mathematics Subject Classification: 35B27, 35Q30, 74Q10, 76M30, 76M50.